PERANAN MOTIVASI TERHADAP KINERJA BIDAN PUSKESMAS PADA EMPAT KECAMATAN DI KABUPATEN TIMOR TENGAH SELATAN - Sanam, Victor E.; Litik, Serlie K.; Pua Upa, Erny E. (Jurnal Pangan Gizi dan Kesehatan, 2010)
Motivation is a stimulating factor for someone to do something by conscious. The role of motivation for performance midwife is important for PUSKESMAS to improve service quality. The general objective of the research is to know the role of midwife motivation performance at four sub-districts in Timor South Center district. The specific objective of the research is to know the description of motivation, midwife performance and the role of motivation in midwife working performance. Descriptive research using a qualitative approach had been used in the research. The population of the research was all midwives at PUSKEMAS for four sub-districts namely, Ayotupas, Niki-Niki, Nulle and Kapan. There were 8 (eight) midwife had been taken for each sub-district as a sample in the research. The result of the research showed that the motivation of midwife based on the need for fulfilment level was very high with an average of 82.28%. The average need for fulfilment levels is physiology 56.25%, sense of security 79.16%, social 96.87%, self-esteem 91.66% and self-actualization 87.5%.